Son and Chosen. A Text-critical Study of John 1,34 - Flink, Timo (Filología neotestamentaria, 2005)
John 1,34 contains a perennial textual problem. Is Jesus depicted as the Son of God, the Chosen One of God, or something else? Previous studies have not been able to solve this problem satisfactorily to all textual critics. This study is a new attempt to resolve it by using a recently noted singular reading in P75*. I argue that this reading changes the transcriptional probabilities. It is lectio difficilior from which all other variant readings derive due second century scribal habits. John 1,34 should read "The Chosen Son". This affects the Johannine theology. This new reading has implications for how to deal with some singular readings elsewhere.